E-146 Retrospective analysis of radiographic exposure and efficacy for three flow-diverter stents. (23rd July 2022) - Williams, A; Abraham, B; Bohnstedt, B; James, R
Abstract : Background: Flow-diverter stents (FDSs) are one method for the embolization of cerebral aneurysms. Our study compared the performance of three flow-diverter stents. Methods: This is a retrospective cohort study of patients with aneurysms who underwent FDS embolization between November 2019 and February 2022. We collected demographics, clinical, peri-operative, and outcome findings by chart review. Aneurysm occlusion rates were scored on the Raymond-Roy occlusion classification scale immediately post-FDS placement and at 6-month follow-up. We conducted univariate analysis to compare the FDS types for these covariates. Results: We analyzed 62 patients with aneurysms treated with Evolve (n = 25, 40.3%), Pipeline (n = 31, 50.0%), and Streamline (n = 6, 9.7%) FDSs. Of aneurysms reviewed, 14 aneurysms (22.6%) were ruptured on admission and 16 aneurysms (25.8%) were a retreatment from a prior intervention. To control for severity of presentation, we stratified our analysis to include only first-time and non-ruptured aneurysms (n = 31) treated with Evolve (n = 20, 64.5%) and Pipeline (n = 11, 35.4%) FDSs. Patients treated with Streamline stents were excluded due to a low sample size upon stratification. We found no statistically significant difference between Evolve and Pipeline stents when assessing intra-operative complication rates. At 6-month follow up, we also report no statistically significant differences when comparing modified Rankin scores, aneurysm occlusion, and rates of in-stent stenosis between Evolve and Pipeline stents (p > 0.05). However, the Evolve stent achieved lower air Kerma dosages and fluoroscopy times (n = 20, 475.5 mGy and 14.35 minutes) compared to the Pipeline stent (n =11, 1933.0 mGy and 37.9 minutes) (p < 0.001). Discussion: In conclusion, our analysis shows that Evolve FDS may provide quicker operative experiences for both the physician and patient. While this does not seem to imply any significant difference in outcome measures from our study, it may provide an economical time benefit to the healthcare setting. Future studies should focus on the clinical significance of this difference. Disclosures: A. Williams: None. B. Abraham: None. B. Bohnstedt: 2; C; Other. R. James: None.